Neural correlates of stress and favorite‐food cue exposure in adolescents: A functional magnetic resonance imaging study. Issue 10 (16th April 2012) - Hommer, Rebecca E.; Seo, Dongju; Lacadie, Cheryl M.; Chaplin, Tara M.; Mayes, Linda C.; Sinha, Rajita; Potenza, Marc N.
<x xml:space="preserve">Abstract</x> Adolescence is a critical period of neurodevelopment for stress and appetitive processing, as well as a time of increased vulnerability to stress and engagement in risky behaviors. This study was conducted to examine brain activation patterns during stress and favorite‐food‐cue experiences relative to a neutral‐relaxing condition in adolescents. Functional magnetic resonance imaging was employed using individualized script‐driven guided imagery to compare brain responses with such experiences in 43 adolescents. Main effects of condition and gender were found, without a significant gender‐by‐condition interaction. Stress imagery, relative to neutral, was associated with activation in the caudate, thalamus, left hippocampus/parahippocampal gyrus, midbrain, left superior/middle temporal gyrus, and right posterior cerebellum. Appetitive imagery of favorite food was associated with caudate, thalamus, and midbrain activation compared with the neutral‐relaxing condition. To understand neural correlates of anxiety and craving, subjective (self‐reported) measures of stress‐induced anxiety and favorite‐food‐cue‐induced craving were correlated with brain activity during stress and appetitive food‐cue conditions, respectively. High self‐reported stress‐induced anxiety was associated with hypoactivity in the striatum, thalamus, hippocampus, and midbrain. Self‐reported favorite‐food‐cue‐induced craving was associated with blunted activity in cortical‐striatal regions, including the right dorsal and ventral striatum, medial prefrontal cortex, motor cortex, and left anterior cingulate cortex. These findings in adolescents indicate the activation of predominantly subcortical‐striatal regions in the processing of stressful and appetitive experiences and link hypoactive striatal circuits to self‐reported stress‐induced anxiety and cue‐induced favorite‐food craving. Hum Brain Mapp 34:2561–2573, 2013. © 2012 Wiley Periodicals, Inc.